Impact of diabetes mellitus in non-ischemic dilated cardiomyopathy: focus on diastolic dysfunction. (3rd October 2022) - Zulet Fraile, P; Ferrandez Escarabajal, M; Islas, F; Travieso Gonzalez, A; Higueras Nafria, J; De Agustin Loeches, A; Vilacosta, I; Olmos Blanco, C
Abstract: Introduction: In patients with diabetes mellitus (DM), the presence of myocardial dysfunction in the absence of coronary artery disease, valvular disease and other conventional cardiovascular risk factors has been defined as diabetic cardiomyopathy. Left ventricle concentric hypertrophy and myocardial fibrosis are the structural hallmarks that lead to overt diastolic dysfunction. The impact of DM in imaging features and clinical outcomes of patients with non-ischaemic dilated cardiomyopathy (DCM) has not been completely elucidated yet. Purpose: We aim to describe advance imaging and clinical characteristics of DCM's patients with DM, and its potential impact on cardiac morphology and function in comparison to non-diabetic patients. Methods: From 2014 to 2021, all patients with DCM were prospectively evaluated in our tertiary care hospital. All patients underwent a transthoracic echocardiogram and 165 patients underwent a 1.5 Tesla scanner cardiac magnetic resonance (CMR) as part of the diagnostic workup. Left ventricle ejection fraction (LVEF), mechanical dyssynchrony, and diastolic function were analyzed according to current guidelines. Late gadolinium enhancement (LGE) was assessed visually and its extent was calculated as the number of affected myocardial segments. Heart failure (HF) hospitalizations, arrhythmic events and mortality were assessed during follow-up. Results: The median age of our cohort (n=227) was 61.6 (14.7) years, 66% were male, and DM was present in 57 patients (25.1%). Mean follow-up was 37.6 (33.9) months. Diabetic patients were significantly older, more frequently male, and with more comorbidity. Left bundle branch block was more frequent in patients with DM. The use of SGLT2 inhibitors was higher in diabetic patients (47.4% vs 21.1%; p<0.05). No significant differences were observed regarding other guideline-recommended HF drugs. With regard to imaging features, no significant differences were found in LVEF and global longitudinal strain between the two groups. There was a trend toward a higher left ventricle mass index measured by CMR in diabetic patients (p=0.364). Parameters of mechanical dyssynchrony and diastolic dysfunction were worse in diabetic patients (Table 1). High-risk LGE pattern (defined as the presence of epicardial, transmural or septal plus free-wall LGE) was more frequently observed in the diabetes group (p<0.05). Finally, the diabetic group had a higher incidence of HF hospitalization (45.61% vs 22%, p<0.001) and all-cause mortality (24.6% vs 11.8%, p<0.05), as shown in Figure 1. There was also a trend toward a higher cardiovascular mortality (12.3% vs 6.5%, p=0.164) in this group. Conclusion: DM confers a high-risk profile to DCM patients, explained by extracardiac (more comorbidities) and cardiac (more diastolic dysfunction and high-risk LGE pattern) reasons. These patients may benefit from a close monitoring, and new therapies should be developed to improve their prognosis. Funding Acknowledgement: Type of funding sources: None.